2017
DOI: 10.1097/eja.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

High quality of evidence is uncommon in Cochrane systematic reviews in Anaesthesia, Critical Care and Emergency Medicine

Abstract: BACKGROUNDThe association between the quality of evidence in systematic reviews and authors’ conclusions regarding the effectiveness of interventions relevant to anaesthesia has not been examined.OBJECTIVEThe objectives of this study were: to determine the proportion of systematic reviews in which the authors made a conclusive statement about the effect of an intervention; to describe the quality of evidence derived from outcomes in reviews that used the Grades of Recommendation, Assessment, Development and Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The previously conducted systematic review also considered secondary outcomes including the extent and duration of virus shedding and viremia, and the results and conclusions were similar to those presented here. For example, our review as well as that performed earlier by Marenzoni et al 54 revealed poor reporting quality of the selected studies. Their meta‐analysis using a random effects model failed to demonstrate that vaccines reduced the number of vaccinated horses with at least one clinical sign following virus challenge infection (pooled RR 0.97, 95% CI 0.86‐1.10, P = .62) with lower heterogeneity ( I 2 = 19%), which contrasts with the results reported here.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The previously conducted systematic review also considered secondary outcomes including the extent and duration of virus shedding and viremia, and the results and conclusions were similar to those presented here. For example, our review as well as that performed earlier by Marenzoni et al 54 revealed poor reporting quality of the selected studies. Their meta‐analysis using a random effects model failed to demonstrate that vaccines reduced the number of vaccinated horses with at least one clinical sign following virus challenge infection (pooled RR 0.97, 95% CI 0.86‐1.10, P = .62) with lower heterogeneity ( I 2 = 19%), which contrasts with the results reported here.…”
Section: Discussionmentioning
confidence: 53%
“…This observation is consistent with some other reviews of the human medical literature. 54,55 Factors that contribute to these lower-quality studies included risk of bias and imprecision. Similar downgrades were applied in the present study for concerns regarding precision, especially as a consequence of underpowered studies for detecting rare events including abortion and neurologic effects.…”
Section: Rating the Overall Quality Of Evidencementioning
confidence: 99%
“…If, for example, the trial authors exploit methodological flexibility to inflate treatment benefits or fail to power a study to detect harmful side effects, the systematic review that summarises this evidence will be unduly optimistic about treatment benefits and harms. Well-conducted systematic reviews can identify some methodological problems in trials: one review of Cochrane reviews found that high quality evidence was available for just 10% of the primary health outcomes examined (Conway et al, 2017 ). As Roberts et al ( 2015 ) point out, systematic reviews’ emphasis on including all relevant trials may be misplaced when so many trials have fundamental methodological flaws.…”
Section: Part Imentioning
confidence: 99%
“…To perform an external validation of our extraction procedures used in data set construction, we used human annotations from the small-scale study by Wilczynski et al [ 39 ], in which various elements were manually extracted from SoFs. Although a larger study was carried out by Conway et al [ 40 ], we were unable to obtain their data. The data set in the study by Wilczynski et al [ 39 ] contains 103 instances (reviews) on anesthesia, critical care, and emergency medicine from the CDSR.…”
Section: Methodsmentioning
confidence: 88%